On a refinement of the convergence analysis for the new exact penalty function method for continuous inequality constrained optimization problem - Yu, Changjun; Teo, Kok Lay; Zhang, L.; Bai, Y. (American Institute of Mathematical Sciences, 2012)
This note is to provide a refinement of the convergence analysis of the new exact penalty function method proposed recently.